The combined effect of Levofloxacin and Azithromycin against multidrug-resistant Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa. - Belal, Progga Parmita (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.